Performance of Geo-synthetic Filter Materials as Drain Envelope in Land Reclamation in Haryana - Lal, Mohan; Arora, V K; Gupta, S K (Journal of Agricultural Engineering, 2013)
Geo-synthetic envelope materials are increasingly replacing gravel/sand in subsurface drainage systems commonly installed to reclaim waterlogged salt affected lands. The availability constraints of gravel/sand envelopes, transport cost, design complexities, application difficulties in mechanized construction helped the switchover to synthetic envelopes, especially geo-synthetic materials. Geo-synthetic envelope materials used in Haryana Operational Research Project (HOPP) were found to be strong enough to withstand handling during transport, manual or machine wrapping, and for use with a drainage pipe laying machine. These materials were tested in the laboratory to characterize them and recommend their use as envelope materials. The field data after 3 and 6 years of installation of the drainage system at Jhajjar in Haryana with geo-synthetic envelope materials revealed much less silting of pipes than the recommended guidelines. The characteristics of a woven synthetic material used to wrap perforated collector pipes are discussed. A machine earlier designed to wrap the geo-synthetic material was evaluated for its capacity. The machine could handle 1.5-2.0 km of pipe daily with 8 semi-skilled labourers, enabling to cope up with the demand of a pipe-laying trencher machine that could lay about 1.5 km of laterals in a single day.